Exploring the Key Elements of Career Well-being: A Qualitative Study based on the new definitions - Sayed-Hadi; Mohammad-Reza Abedi; Parisa Nilforooshan (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Career well-being is one of the elements of positive psychology which could enhance one's flourishing and development in life. The objective of this study was to explore the key elements of career well-being based on the new definitions in this field. Materials and Methods: The present study was of qualitative design with exploration method. The statistical population included all employees of Shahid Beheshti University in Tehran, from whom 73 people were selected via purposeful sampling. Data were gathered using interview method and thematic analysis technique was used for data analysis. Results: The mean (SD) age of participants was 38 (8.8). Among participants, 34 (46.6%) were women and 39 (53.4%) men. As many as 31 (42.5%) had less than 10 years of work experience and 42 (57.5%) had more than 10 years of work experience. The key elements of  career well-being among employees of Shahid Beheshti University included: a sense of satisfaction and happiness to career (65.7%), positive interpersonal relationships (58.9%), engagement (52%), positive organizational relationships (50.6%), job performance (42.4%), work-life balance (39.7%), learning and development (36.9%), career transitions (30.1%), emotional stability (28.7%), sense of purpose and meaning (24.6%), fulfillment and competence (21.9%), and environmental mastery (19.1%). Conclusion: The study showed that a sense of satisfaction and happiness to career, positive interpersonal relationships, engagement, positive organizational relationships, job performance, work-life balance, learning and development, career transitions, emotional stability, sense of purpose and meaning, fulfillment and competence, and environmental mastery were the key elements of career well-being among the employees of Shahid Beheshti University in Tehran.